Verbal and Visual Communication Elements Used in Music Video Clip - Jandinhi, Desak Komang Kharisma; Beratha, N. L Sutjiati; Netra, I Made (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana; Vol 28 No 2 (2021) : SeptemberDO - 10.24843/ling.2021.v28.i02.p09, 2021)
The recent study is aimed to analyze and find the use of verbal and visual communication elements and also the correlation between the visual elements and verbal representation with the meaning of the song. This study used documentation method in collecting the data . T he data were colected through three steps : first, downloading the data from the internet ; second, watch ed and listen ed carefully the music and continue d to read the song lyrics repeatedly ; third, finding the sign of meaning and classified the data according to their type ; and for the last part, the message that stand behind the sign were analyzed. The data was using the descriptive qualitative method based on the analysis and the theory of visual communication elements proposed by Dyer (1993) and the theory of meaning proposed by Leech (1974).